Evaluation of Combinational Therapy of L-Arginine with Some Phenolic Acids in Paclitaxel-induced Neuropathic Pain - Pawar, Shubhangi; Pagare, Amrapali; Katti, Suvarna; Patil, Rupali; Tayde, Manisha (Asian Journal of Biological and Life Sciences)
Background: Paclitaxel is an anticancer drug that can induce neuropathy and is used in animal models to evaluate new therapeutic approaches in neuropathy. Paclitaxel increases oxidative stress, which is a key contributor to the pathogenesis of neuropathy. Many phenolic acids as well as amino acids with antioxidant potential are proven as neuroprotective. Objectives: To evaluate combinational therapy of L-Arginine with Syringic acid and Sinapic acid, separately in paclitaxel-induced neuropathy by assessing behavioral and biochemical parameters. Materials and Methods: Wistar rats were divided into seven groups (n=6). Neuropathic pain was developed with Paclitaxel (2mg/kg, i.p), repetitively administered on the 1st, 3rd, 5th, and 7th days in rats. Treatment with phenolic acids, L-Arginine and Gabapentin was started along with paclitaxel from day first for 5 weeks. Behavioural study (mechanical and thermal hyperalgesia, allodynia and motor co-ordination) was carried out weekly by using Von Frey filaments, Rota rod apparatus, hot plate and cold plate. Biochemical study (MDA, GSH, SOD) was performed after sacrification at the end of the study. Results: A combination of L-Arginine with syringic acid and sinapic acid has shown a significant reversal of behavioural changes and oxidative stress induced by paclitaxel. L-Arginine has potentiated individual effects of syringic acid and sinapic acid. Conclusion: The results suggested antioxidant, analgesic and neuroprotective effects in combinational therapy of L-Arginine. This study is indicating that combination of L-Arginine could be beneficial to reduce dose requirement of syringic acid and sinapic acid in treatment of neuropathic pain.
Keywords: L-Arginine; Neuroprotective effect; Paclitaxel; Sinapic Acid; Syringic acid